What is communication assistance? Describing a new and emerging profession in the New Zealand youth justice system. Issue 2 (3rd March 2020) - Howard, Kelly; McCann, Clare; Dudley, Margaret
Abstract : 'Communication assistance' is a term that derives from section 80 of the Evidence Act 2006: a legislative provision that has given birth to a whole new profession in the New Zealand legal system. This legislative provision has been used to appoint a new role: that of the communication assistant to support complainants, witnesses and defendants of all ages with identified communication needs. This study focuses specifically on the provision of communication assistance for young people who offend in the New Zealand criminal justice system. It provides a qualitative analysis of professionals' descriptions ( n = 28 participants) of communication assistance for this population in justice processes. The findings illustrate that communication assistance shares its core with a similar role in England and Wales, that of the intermediary, but that communication assistants in New Zealand have broader scope than their counterparts working in the area of youth justice.